Length structure of ictiofauna in a tropical estuary (Pernambuco-Brazil) - de Oliveira Lima, Severino Adriano; Andrade, Humber Agrelli; da Fonseca Albuquerque, Paulo de Tarso; Garcez Costa Sousa, Raniere (Arquivos de Ciências do Mar, 2022)
Estuaries are habitats favorable to occupation by several species of fish, due to the availability of shelter and nutrients. Among the various fishery resource management tools, studies based on the size of specimens are useful for a better understanding of the structure of the estuarine community. Also, they can be associated with reproductive aspects and selectivity of fishing gears, useful for mitigating the effects of overfishing. In the present study, the lengths of fish species captured with gillnet were spatially assessed in a tropical estuary in the state of Pernambuco, in horizontal stretches (center and margins) and depths (upper, intermediate, and lower) between July 2013 and June 2014. Among the most captured fish species, juvenile individuals were predominant in the species Chloroscombrus chrysurus Harengula clupeola, Lycengraulis grossidens, Opisthonema oglinum and Anchovia clupeoide, which had an average length of 6.47 cm, 9.59 cm, 9.93 cm, 11.25 cm and 12.17 cm, respectively, while Strongylura marina occurred adult individuals who had a mean length of 42.43 cm. The length structure of the main fish was composed of juveniles, but the lengths were longer in the dry season for the most caught species O. oglinum and A. clupeoides. The maximum lengths found for O. oglinum were twice as short as those found in the 1970s. Therefore, there is a need to implement measures that aim to protect the estuary of the Santa Cruz Channel in order to conserve fish stocks in the region. Keywords: Clupeidae, artisanal fishing, pelagic fish, gillnet.